Health Behavior among Health Promotion Officers at Primary Health Care in East Kalimantan - Riza Hayati Ifroh; Indah Nur Imamah (Universitas Muhammadiyah Semarang, 2022)
Background: A health promotion officer or health educator as well-being proficient has an essential well-being care in supporting and empowering the community of health behavior. They are real examples in the community required to progress the quality of life and diminish the risk of non-communicable illnesses. Aim: To assess the different levels of health-promoting lifestyle based on socio-demography, working experiences, and body mass index among health promotion officers in primary health care in East Kalimantan. Method: A cross-sectional study was performed with data collected by socio-demography, working experience, BMI, and Health-Promoting Lifestyle Profile II (HPLP II) of six dimensions. Data was taken by an online self-administered questionnaire. Participants were recruited by convenience sampling on 74 health promotion officers at 191 of primary health care in East Kalimantan. The descriptive and inferential statistics were analysis approaches. Result: Mean score of 2.99 (good) for total HPLP (67.6%). As overall, there were no differences between HPLP with socio-demographic (p-value: 0.293); working experiences (p-value: 0.098) and BMI (p-value: 0.396). In detailed, there were differences statistically in physical activity between gender (p-value = 0.016), and the residence (p-value = 0.007). There were differences statistically in nutrition (p-value = 0.043), and interpersonal relationship (p-value = 0.011) based on marital status. Conclusion: Since the HPLP indicators scores were good, there is a need to enhance and promote a healthy lifestyle. Further identification is needed to determine the causes of lack causes of nutrition and physical activity. Aspects that must be maintained are health responsibilities, interpersonal relationships and spiritual growth.